Efektivitas Penerapan Media Pembelajaran PhET Dalam Mengatasi Tingkat Kesulitan Mahasiswa Pada Mata Kuliah Fisika Dasar I - Sari, Agung Suci Dian (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effectiveness of the application of PhET learning media in overcoming the level of difficulty of students in Basic Physics I courses. The application of PhET learning media is applied to students of Physics Education SI. This type of research is a quantitative study with a research design using the One Group Pre-test and Post-test design. Data collection techniques through tests and questionnaires. The results showed that there was an increase in the pre-test and post-test of 0.79 in the high category, the results of the Pairet T-Test showed that there was a difference between the pre-test and the post-test with sig. (2-tailed) <5%, and the results of the questionnaire response were in the very good category. So that the application of PhET learning media is effective to be applied in overcoming the level of difficulty of undergraduate physics education students in Basic Physics I courses.